Sustainable Development Methodology: A methodical approach to innovation that encourages creativity and strategy in the promotion of organizational alternatives - Prasad, Dr. KDV; Mangipudi, Dr. Mruthyanjaya Rao (The journal of contemporary issues in business and government, 2022)
In the study that has been conducted on a methodical approach to innovation through sustainable development methodology, the authors majorly focused upon three components: business process reengineering, strategic business units, and the leadership that plays a critical role in being innovative and creative thereby generating organizational alternatives. Organizational alternatives shall always be explored depending on the business needs through which they see the future for the organization’s sustainability. The authors explore the significance of these three components and the associated elements surrounding sustainable development methodology with reference to leadership in this article. The components will significantly contribute to the creativity and promotion of organizational alternatives.